Demand Postponement with Strategic Service Customers. (February 2022) - Wang, Haiyan; Olsen, Tava Lennon; Shalpegin, Timofey
Highlights: Strategic customers exhibit a "follow-the-crowd" type of behavior. The presence of strategic customers does not benefit the service provider. The service provider might need to build excess capacity. The presence of strategic customers may benefit the peak-time customers. Abstract: We study capacity decisions in a service environment with seasonal arrival rates and strategic customers. Due to seasonality, the firm uses a postponement strategy where compensation is given to the peak-time customers who cannot be served in the peak time and agree to delay service. We extend the analysis of demand postponement to the case with strategic customers, i.e., off-peak customers who may pretend to be peak-time customers purely to receive the postponement discount. Focusing on the capacity and discount decisions for the service provider, we develop a game-theoretic model to study when the service provider should consider using a postponement strategy in the presence of strategic customers. At the first stage, the service provider decides on the capacity level and discount. At the second stage, strategic customers decide whether to show up in the peak time. We find that strategic customers exhibit a "follow-the-crowd" type of behavior. Unsurprisingly, we find that the presence of strategic customers does not benefit the service provider. More interestingly, we find that the presence of strategic customers may benefit the peak-time customers, unlike the inventory literature with strategic (arrival-timing) customers, in which the supplier's response is usually detrimental to non-strategic customers. In the presence of strategic customers, the supplier needs to offer a lower discount or build more capacity than without strategic customers. If the supplier does not have control over the discount value, she might need to build excess capacity to prevent the strategic customers from showing up in the peak time.